Improvement of Fine Motor Competence Competence with Activities Coloring - Adinda Amalia Pramesti (Universitas Pendidikan Indonesia, 2022)
Fine motor development is very important for a child's overall development. Kindergarten-age children still often have difficulty moving their fingers for activities such as cutting, drawing, tearing, folding, arranging and filling patterns by pasting small objects. The improvement is inseparable from the learning steps, namely: (1) One class is divided into three groups consisting of four to five children (2) Each group gets four to five kinds of dyes and crayon media that have been put into containers (3) examples of coloring activities that will be carried out (4) Delivering the agreed rules during coloring activities and (5) Color drawings adjusted to the ongoing theme in kindergarten.